Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 3 - Differentiation - 3.3 Product and Quotient Rules - Preliminary Questions - Page 121: 3


$g(1) = 5$

Work Step by Step

By product rule, we know that: $(fg)' = f'g + g'f$ By substituting the values we are given into the equation above we get: $10 = 2g(1) + 0g'(1)$ And then we can simplify to get: $10 = 2g(1)$ $g(1) = 5$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.